Colostomy closure in pediatric age group A comparative study between Single and double layer anestomosis - Abdul-Gafoor, Bilal Hamid; Al-Dabbagh, Hussain Malik (Journal of the Faculty of Medicine Baghdad, 2007)
This prospective study involved one hundred patients with colostomies admitted at the Central Pediatric Teaching Hospital for colostomy closure over the period of two years (Jan.2000- Jan2002). Patients were divided in to two groups according to the technique of colostomy closure. In the first group, the closure was done by single layer of interrupted non-absorbable suture material; in the second group closure was done by double layer suturing technique. All patients were prepared by the same conventional method including fluid diet for three days followed by two days washing enemas before operation with antimicrobial prophylaxis agents. Of these one hundred patients;(48) presented as cases of Hirschsprung`s disease, (50) were cases of ano-rectal malformations, and (2) were cases of traumatic colonic perforation. According to the type of the colostomy; there were (62) loop colostomy, and (38) double-barreled colostomy. According to the site of the colostomy; there were (84) patients with right transverse colostomy, (2) with left descending colostomy, (12) with sigmoidostomy, and (2) with cecostomy. Sixteen patients developed complications following colostomy closure; these were (wound infection, fecal fistula, small bowel obstruction, and other systemic infections). We advise single layer bowel anastomosis for the following reasons: 1-operative time (anesthetic time) theoretically shorter with single layer closure. 2-less tissue handling (less trauma) with single layer closure. 3-less narrowing effect (as less suture material) on the already small bowel lumen. Too many sutures and too many knots leading to comprise blood supply with double layer closure. 4-more cost benefit with single layer closure.